2015
DOI: 10.1590/1413-81232015207.17972014
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica das relações familiares intergeracionais na ótica de idosos residentes no Município de Jequié (Bahia), Brasil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 7 publications
3
11
1
14
Order By: Relevance
“…Although other studies have related social support to the household arrangement (Alves et al, 2015;Borges & Magalhães, 2011;Paúl, 2005;Rabelo & Neri, 2015;Rosa et al, 2007) in this study there were no statistically significant associations between these variables. It was observed that the sample tended to have a high availability of self-perceived social, instrumental, affective, informative and social-emotional support.…”
Section: Discussioncontrasting
confidence: 84%
“…Although other studies have related social support to the household arrangement (Alves et al, 2015;Borges & Magalhães, 2011;Paúl, 2005;Rabelo & Neri, 2015;Rosa et al, 2007) in this study there were no statistically significant associations between these variables. It was observed that the sample tended to have a high availability of self-perceived social, instrumental, affective, informative and social-emotional support.…”
Section: Discussioncontrasting
confidence: 84%
“…In the report of these children, another reason for not expecting care is the change in the values of the current generation, which takes children away from the role of caregivers. A study carried out in the state of Bahia/Brazil also found that in the care of the aged, sometimes conflicts arise because the aged has experienced other cultural contexts, with their beliefs that differ from the younger generations (20) . In this sense, Brazil has been undergoing several social changes, impacting directly on culture, in the sense of dealing with situations.…”
Section: Discussionmentioning
confidence: 99%
“…(P23) Respaldando esse entendimento, outros estudos também ressaltaram, entre as causas de problemas familiares, as diferenças de crenças, culturas e visão de mundo intergeracionais que geram insatisfação dos idosos com netos e filhos, culminando em conflitos diante da discordância em torno de comportamentos. 30,31 Assim, a violência contra a pessoa idosa passa pela perda de espaço dentro da família, pela incompreensão das pessoas quanto ao declínio das capacidades físicas e mentais, que aliadas aos estereótipos, atribuem ao idoso a pecha de inútil. Tudo isso culmina na indignidade de ser tratado como alguém que, devido ao avanço dos anos, vai aos poucos perdendo suas prerrogativas de ser humano.…”
Section: "O Mais Comum Na Minha Realidade Em Relação à Violência Com unclassified